Vaccine refusal - what we need to know - Regina Célia de Menezes Succi (Brazilian Society of Pediatrics, 2018)
Objective: Opposition to vaccines is not a new event, and appeared soon after the introduction of the smallpox vaccine in the late 18th century. The purpose of this review is to educate healthcare professionals about vaccine hesitancy and refusal, its causes and consequences, and make suggestions to address this challenge. Source of data: A comprehensive and non‐systematic search was carried out in the PubMed, LILACS, and ScieLo databases from 1980 to the present day, using the terms "vaccine refusal," "vaccine hesitancy," and "vaccine confidence." The publications considered as the most relevant by the author were critically selected. Synthesis of data: The beliefs and arguments of the anti‐vaccine movements have remained unchanged in the past two centuries, but new social media has facilitated the dissemination of information against vaccines. Studies on the subject have intensified after 2010, but the author did not retrieve any published studies to quantify this behavior in Brazil. The nomenclature on the subject (vaccine hesitancy) was standardized by the World Health Organization in 2012. Discussions have been carried out on the possible causes of vaccine hesitancy and refusal, as well as on the behavior of families and health professionals. Proposals for interventions to decrease public doubts, clarify myths, and improve confidence in vaccines have been made. Guides for the health care professional to face the problem are emerging. Conclusions: The healthcare professional is a key element to transmit information, resolve doubts and increase confidence in vaccines. They must be prepared to face this new challenge. Resumo: Objetivo: Oposição às vacinas não é evento novo e surgiu logo após a introdução da vacina contra varíola no fim do século XVIII. O objetivo desta revisão é esclarecer os profissionais de saúde sobre hesitação e recusa vacinal, suas causas e consequências e fazer sugestões para enfrentar esse desafio. Fonte dos dados: Foi feita busca abrangente e não sistemática nas bases de dados PubMed, Lilacs e Scielo desde 1980 até o presente, com os termos "recusa vacinal", "hesitação vacinal" e "confiança nas vacinas". Foram selecionadas de forma crítica as publicações avaliadas como mais relevantes pela autora. Síntese dos dados: As crenças e os argumentos dos movimentos antivacinas mantiveram‐se inalterados nos dois últimos séculos, mas as novas mídias sociais facilitaram a disseminação das informações contra as vacinas. Os estudos sobre o assunto se intensificaram depois de 2010, mas não foram identificados estudos publicados que permitam quantificar esse comportamento no Brasil. A nomenclatura sobre o tema (hesitação vacinal) foi uniformizada pela Organização Mundial de Saúde em 2012. Pesquisas têm sido feitas sobre as possíveis causas da hesitação e recusa vacinal, e também sobre o comportamento das famílias e dos profissionais da saúde. Propostas de intervenções para diminuir as dúvidas da população, esclarecer mitos e melhorar a confiança nas vacinas têm sido feitas. Guias para o profissional de saúde enfrentar o problema estão surgindo. Conclusões: O profissional de saúde é elemento fundamental para transmitir informações, combater as dúvidas e fortalecer a confiança nas vacinas. Eles devem se preparar para enfrentar esse novo desafio. Keywords: Vaccination, Vaccine refusal, Vaccine hesitancy, Vaccine confidence, Vaccine acceptance, Palavras‐chave: Vacinação, Recusa vacinal, Hesitação vacinal, Confiança nas vacinas, Aceitação das vacinas